The Effects of Climate Change on Natural Water Resources: A Health Crisis - Sejabaledi Agnes Rankoana (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
The provision of sustainable, high-quality, and safe water is imperative for a healthy and good life for all living beings. Limited supply, increased demand, and declining water quality can adversely affect community members' health and well-being. This research investigated the impacts of climate change on local water sources and the subsequent effect of water scarcity on the health of a rural community in Limpopo Province, South Africa. Results from a study involving 53 randomly selected individuals in a rural community indicate that the most severe health issues caused by a lack of water include poor sanitation and hygiene-related disorders such as lice infestations, cholera, malaria, diarrhoea, dysentery, and skin infections. This study recommends that the South African government provide the necessary resources to ensure unrestricted access to sustainable and high-quality water to meet Sustainable Development Goal 6.